Managerial Competence of School Principals in Implementing Total Quality Management: A Study of Elementary Schools in Meurah Mulia - Darmayanti, Darmayanti; Marwan, Marwan; Najmuddin, Najmuddin (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
In a period of increased educational rivalry and accountability, schools need to employ management strategies that ensure continual quality improvement. Total Quality Management (TQM) has emerged as a strategic paradigm for improving educational services using systematic, data-driven, and participative methods. This study looks into the managerial skills of school principals in implementing TQM at public elementary schools in Meurah Mulia Subdistrict, Aceh Utara, Indonesia. Data were acquired using a qualitative study design, including in-depth interviews, observations, and document analysis with administrators, teachers, and parents. The findings show that principals' managerial competence—conceptual, human relations, and technical skills—plays an important role in implementing TQM concepts in daily school activities. Among these categories, technological abilities, particularly those related to educational technology and data systems, stand out the most. However, the analysis also highlights problems in collaborative culture and shared responsibility for quality improvement. This study contributes to the developing discussion on educational leadership by emphasizing that effective TQM implementation in schools is dependent additionally on policy adoption, but also on the principal's capacity to integrate managerial expertise into a sustainable culture of quality. The report proposes that school leaders receive systematic professional development to improve their interpersonal communications skills and encourage deeper stakeholder participation.